Influence of MWCNT-f as a UV protective layer in polymer composites with TGDDM/DDS for space application - Edwards, E. R.; Botelho, E. C. [UNESP]; Braga, N. A. (Springer Nature, 2022)
In this work, were evaluated the influence of UV radiation on the chemical structure of the composite fabricated with epoxy resin N,N,N`,N`- tetraglycidyl-4,4` diaminodiphenylmethane (TGDDM) and the hardener 4.4` diaminodiphenyl sulfone (DDS) for space application. Carbon nanotubes were functionalized with acyl chloride (SOCl2) and by varying the nanostructured composites were processed by using epoxy resin with MWCNT-f in varying percentages. The penetration depth of UV radiation in composites exposed in a UV camera for 4320 h was evaluated by Fourier transform infrared spectroscopy (FTIR) coupled with attenuated total reflectance (ATR) coupled. Structural characterizations were performed with Scanning Electron Microscopes (SEM). The analysis of protection against the degradation of polymeric chains was evaluated with the addition of increasing amounts of functionalized carbon nanotubes (MWCNT-f). It was observed that with the addition of 1% MWCNT-f there was a better formation of barriers against the penetration of UV avoiding the degradation of the material.
Keywords: Chemical properties; Nanostructures; Surface analysis; UV radiation